Tangible tele-meeting system with DV-ARPN (Augmented Reality Peripheral Network) - Kwon, YM; Park, JW (SPRINGER-VERLAG BERLIN, 2005)
In this paper, we introduce our researches on tele-meeting system that supports the network interaction with augmented reality. Our system supports networked haptic handshakes for the greeting, networked AR (Augmented Reality) for the augmenting the remote real object with the virtual object, and the network interaction share to the virtual object among participants using VRPN (Virtual Reality Peripheral Network). First, we describe a haptic-based network handshake that enables us to use the sense of sight, hearing, and touch all together with haptic device and video conferencing. Second, we present a networked AR system that supports augmentation of remote real object with local virtual object using ARToolKit and DV video streaming technique using DVTS. This makes AR system be possible with the situation that real object does not exist local area. Third, we propose a networked interaction with AR that supports the share of interactions to the virtual object that is augmented to the real object using AR technique. This concept provides interaction to virtual object at any participants and supports the share of the interaction result with all the participants in the network. The AR and network interaction concepts are integrated and implemented using ARToolKit, VRPN and DVTS. Here, we call it as DV-ARPN (Augmented Reality Peripheral Network).